Analisis Regresi Linier Sederhana dan Berganda Beserta Penerapannya - Muh Alwy Yusuf; Herman Herman; Trisnawati. H; Ardy Abraham; Hardianti Rukmana (Departement of Mathematics Education, 2024)
This research is included in the type of causal associative research. The stages of this research on simple linear regression analysis and multiple linear regression are as follows: Variable Identification, Data Analysis then data processing using SPSS software. From the results of the simple regression analysis